Impact of the China Healthy Cities Initiative on Urban Environment. - Yue, Dahai; Ruan, Shiman; Xu, Jin; Zhu, Weiming; Zhang, Luyu; Cheng, Gang; Meng, Qingyue (Journal of Urban Health, 2017)
The China Healthy Cities initiative, a nationwide public health campaign, has been implemented for 25 years. As "Healthy China 2030" becomes the key national strategy for improving population health, this initiative is an important component. However, the effects of the initiative have not been well studied. This paper aims to explore its impact on urban environment using a multiple time series design. We adopted a stratified and systematic sampling method to choose 15 China healthy cities across the country. For the selected healthy cities, 1:1 matched non-healthy cities were selected as the comparison group. We collected longitudinal data from 5 years before cities achieved the healthy city title up to 2012. We used hierarchical models to calculate difference-in-differences estimates for examining the impact of the initiative. We found that the China Healthy Cities initiative was associated with increases in the proportion of urban domestic sewage treated (32 percentage points), the proportion of urban domestic garbage treated (30 percentage points), and the proportion of qualified farmers' markets (40 percentage points), all of which are statistically significant (P < 0.05). No significant change was found for increases in green coverage of urban built-up area (5 percentage points), green space per capita (2 square meter), and days with Air Quality Index/Air Pollution Index ≤ 100 (25 days). In conclusion, the China Healthy Cities initiative was associated with significant improved urban environment in terms of infrastructure construction, yet had little impact on green space and air quality.